The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s19061277
|View full text |Cite
|
Sign up to set email alerts
|

A Technological Review of Wearable Cueing Devices Addressing Freezing of Gait in Parkinson’s Disease

Abstract: Freezing of gait is one of the most debilitating symptoms of Parkinson’s disease and is an important contributor to falls, leading to it being a major cause of hospitalization and nursing home admissions. When the management of freezing episodes cannot be achieved through medication or surgery, non-pharmacological methods such as cueing have received attention in recent years. Novel cueing systems were developed over the last decade and have been evaluated predominantly in laboratory settings. However, to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 98 publications
1
63
0
6
Order By: Relevance
“…Nine of 12 participants were willing to use Google Glass at home to address FOG. Recently, Sweeney et al reviewed wearable cueing devices delivering visual, auditory or vibration cue and addressing FOG in PD in recent years, and found that cueing was generally effective and promising [163]. However, it should be noted that some devices although seems promising, efficacy of various cueing devices need to be further tested outside the home or laboratory and in a larger PD patients with FOG.…”
Section: Physiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of 12 participants were willing to use Google Glass at home to address FOG. Recently, Sweeney et al reviewed wearable cueing devices delivering visual, auditory or vibration cue and addressing FOG in PD in recent years, and found that cueing was generally effective and promising [163]. However, it should be noted that some devices although seems promising, efficacy of various cueing devices need to be further tested outside the home or laboratory and in a larger PD patients with FOG.…”
Section: Physiotherapymentioning
confidence: 99%
“…Multicenter, double-blind, placebo/sham-controlled randomized trials are needed to confirm theses exciting and promising findings. Of physiotherapy, wearable cueing devices was generally effective and promising [163]. However, the efficacy of various cueing devices need to be further tested outside the home or laboratory and in a larger PD patients with FOG.…”
Section: Summary Of Non-pharmacological Treatments For Fogmentioning
confidence: 99%
“…This results in increased neuronal firing activity in the output nuclei of the basal ganglia that leads to excessive inhibition of thalamo-cortical and brainstem motor systems which, in turn, interferes with movement onset and execution [28,29]. (B) Representation of brain areas activated during external cueing reported from findings of image analysis studies conducted on people with PD during cueing experiments [17,[30][31][32].…”
Section: Pathophysiology Of Motor Dysfunction In Pdmentioning
confidence: 99%
“…The hypothesized neural mechanism for external cueing, suggested by Morris et al [92], bypasses the hypoactive basal ganglia-supplementary motor cortex (SMA) circuit by slightly altering the way the neural circuits control movement in individuals with PD [31,35,99]. In general, sensory cues are known to enable the dorsolateral pre-motor control system [30,32,63] which bypasses the SMA that is deficient in PD. Specifically, it has been suggested that auditory cues help in improving the temporal parameters, such as cadence and gait speed, and that external cues help because they are able to bypass the internal rhythm deficit associated with PD.…”
Section: Different Cueing Types May Engage Different Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation